Developing a Photoacoustic Whole-Breast Imaging System Based on the Synthetic Matrix Array - Zhang, Guangjie; Li, Wenzhao; Yang, Meng; Li, Changhui (Frontiers in Physics, 2020)
In this study, we reported a photoacoustic (PA) imaging system for whole-breast imaging. Similar to the traditional X-ray mammography, this system slightly compressed the breast by a water tank. The PA signal is acquired via scanning a long unfocused ultrasonic linear array probe over the breast top surface, and the expanded high-energy laser pulses illuminate the breast bottom through a transparent supporting plate. Scanning the unfocused transducer probe is equivalent to a synthetic two-dimensional (2D) matrix array, which significantly increased the field of view (FOV) via a much easier way and at a much lower cost. Our phantom results demonstrated that this system has a great potential for clinical implementation.